2018
DOI: 10.1002/2017jd027758
|View full text |Cite
|
Sign up to set email alerts
|

A Null‐Parameter Formula of Storage‐Evapotranspiration Relationship at Catchment Scale and its Application for a New Hydrological Model

Abstract: Different formulas have been developed to estimate the mean annual evapotranspiration ratio (E/P) from the mean annual aridity index (Ep/P) based on the Budyko framework. A major challenge in using the Budyko framework for the interannual behaviors of a catchment is the missed storage. Here we develop a null‐parameter formula of the storage‐evapotranspiration relationship based on the simplified proportionality hypothesis, which takes the storage in the soil‐plant‐atmosphere continuum as the accessible water f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Models in Han et al. (2018), Istanbulluoglu et al. (2012), Thomas (1981) as well as Wang and Zhou (2016) could be used to do simulation, but it is difficult to distinguish the impact of croplands from generalized model parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Models in Han et al. (2018), Istanbulluoglu et al. (2012), Thomas (1981) as well as Wang and Zhou (2016) could be used to do simulation, but it is difficult to distinguish the impact of croplands from generalized model parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Inter‐annual variation in the water balance has been investigated in many studies (Arora, 2002; Han et al, 2018; Istanbulluoglu et al, 2012; Koster & Suarez, 1999; Yang et al, 2007). It has been found that the inter‐annual variability in streamflow is mainly controlled by the inter‐annual variability of climate, especially in humid regions (Milly & Dunne, 2002; Xu et al, 2012; Yang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, calculated effective rainfall replaces rainfall in both the climate aridity index and the evaporation ratio. Recently, Han et al [24] proposed a null-parameter formula of the storage-evapotranspiration relationship based on a simplified proportionality hypothesis. However, the attribution analysis methods used in these studies were mostly based on Budyko decomposition [25] and few studies have applied hydrological sensitivity analysis to seasonal runoff attribution.…”
Section: Introductionmentioning
confidence: 99%